STRATEGI MENGHADAPI COBAAN DALAM AL-QUR’AN (Pemaknaan Tekstual dan Kontekstual terhadap Qs. Al-Baqarah : 155) - Afandi, Irfan; Mahmud, M. Amir (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2020)
Humans will definitely get a trial or disaster. The study of the trials of Allah SWT in the Qur'an is more about the justification of good and bad, there are still rarely studies that mention how the strategy of being a "survivor" of the trial of Allah SWT. This study will try to initiate a study on Qs. Al-Baqarah : 155. The approach used to understand this verse is language study; starting with the study of vocabulary from verses, morphology to the study of the structure of Arabic language. Allah SWT will try in five (5) types of trials, namely fear, hunger, lack of wealth, lack of life (death / health) and lack of fruits (staple foodstuffs). In the study of the letter 'wawu' in the verse, one gets an understanding of which time the trial comes first and which trial comes later. Fear and hunger are trials that are coming for the first time. After that, there will come the next type of trial. By knowing the phases when trials come, humans can develop strategies in order to minimize the other 3 (three) trials. So, humans can become survivors of the trials of Allah SWT.